RISK ASSESSMENT BY STRUCTURAL ANALYSIS AND VIBRATION MEASUREMENT EQUIPMENT OPERATING AT OIL FACILITIES - Marius STAN (Fiabilitate şi Durabilitate)
Vibration analysis applications in operation is one of the diagnostic methods ofoperation of the facility. Analysis of these types of failures indicated the existence of specificfeatures prints and related equipment vibration spectra. Modeling and identification of theseparticular aspects in the spectrum of vibration machines help to control the operation of oilfacilities built safely.